Manganese encephalopathy: utility of early magnetic resonance imaging. - Nelson, K (1993)
The use of magnetic resonance imaging (MRI) provides visual evidence of cerebral deposits of paramagnetic metals. The usefulness of MRI is described in connection with the manganese poisoning of a 44 year old arc welder who had been engaged in the repair and recycling of railroad track made of manganese steel alloy.